2000
DOI: 10.1002/1097-0177(2000)9999:9999<::aid-dvdy1043>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous activation of 10 muscle‐specific protein (MSP) genes during zebrafish somitogenesis

Abstract: A methodology for screening either various catalysts for a given metathesis reaction, i.e., ring opening‐ring closing alkene metathesis (RO‐RCM) and cross‐metathesis (CM), or various substrates for a given pre‐catalyst on a thin layer chromatography (TLC) plate has been developed. As the substrates elute with the solvent, this TLC‐based system acts as a heterogeneous catalyst bed (“TLC reactor”). Selected promising catalyst candidates were screened on a TLC plate and their initial catalytic potential as observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 26 publications
14
109
0
Order By: Relevance
“…␣-actin is a thin filament gene (Xu et al, 2000); tnnt1 was expressed in both slow and fast muscles, whereas tnnt3b expression was fast-muscle specific. Our results show that ␣-actin and tnnt1 transcripts were strongly detectable in the entire somites of WT embryos (Fig.…”
Section: Knockdown Of Mrf4 Causes Myofibrils Misalignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…␣-actin is a thin filament gene (Xu et al, 2000); tnnt1 was expressed in both slow and fast muscles, whereas tnnt3b expression was fast-muscle specific. Our results show that ␣-actin and tnnt1 transcripts were strongly detectable in the entire somites of WT embryos (Fig.…”
Section: Knockdown Of Mrf4 Causes Myofibrils Misalignmentmentioning
confidence: 99%
“…NM_181499), tnnt3b (NM_181653), ␣-actin (Xu et al, 2000), myf5 (Chen et al, 2001), mrf4_tv1 and mrf4_tv4 (this study) were used as probes. They were digoxigenin-labeled, after we cloned their partial DNA fragments.…”
Section: Fish Embryos Whole-mount In Situ Hybridization and Cryosecmentioning
confidence: 99%
“…It has been shown that the fiber type composition of individual muscles and expression of MLC changes dramatically during fish ontogeny [4]. The expression of the MyHC and MLCs is asynchronous during the Zebrafish muscle development [5]. In rainbow trout, none of the MLC transcripts were detected before stage 12 (20 somites).…”
Section: Introductionmentioning
confidence: 99%
“…Several fmyhc genes have been identified, but the expression of at least some of the genes can initially be observed both in adaxial cells and in the fast muscle domain and will later during development become more fibre type-specific (Bryson-Richardson et al, 2005). In addition, more specific fast fibre markers encoding sarcomeric proteins have been identified, such as troponinT3a (tnnt3a), tnnt3b, myhz1 (fmyhc1.1), and the myosin light chains mylz2 and mylz3 (Xu et al, 2000, Hsiao et al, 2003. However, the expression pattern during early stages of fast differentiation has not been established, and the transcription initiation occurs later for some of these genes and can initially be detected at stages between 14-16 somites (Xu et al, 2000;Hsiao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more specific fast fibre markers encoding sarcomeric proteins have been identified, such as troponinT3a (tnnt3a), tnnt3b, myhz1 (fmyhc1.1), and the myosin light chains mylz2 and mylz3 (Xu et al, 2000, Hsiao et al, 2003. However, the expression pattern during early stages of fast differentiation has not been established, and the transcription initiation occurs later for some of these genes and can initially be detected at stages between 14-16 somites (Xu et al, 2000;Hsiao et al, 2003). Also, a commonly used protein marker for fast muscle fibres is the F310 antibody (DSHB), which was originally generated by Crow and Stockdale (1986).…”
Section: Introductionmentioning
confidence: 99%